2018
DOI: 10.18332/tpc/101577
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of a 3-day residential treatment for smoking cessation in Hong Kong

Abstract: INTRODUCTION The Tung Wah Group of Hospitals Integrated Centre on Smoking Cessation has been providing free smoking cessation services since 2009. The average quit rate from 2009 to 2014 was 37%. In order to boost the quite rate, we have implemented a residential treatment program for smokers who volunteered to participate. Having run the program for two years, we conducted a retrospective cohort study to evaluate its effectiveness. METHODS We recruited the participants who had failed previous quit attempts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 22 publications
(16 reference statements)
1
16
0
4
Order By: Relevance
“…In the meantime, those ever having cessation advice from others and with shorter smoking years were associated with higher forward transition for those in the preparation stage. These results are consistent with Ho et al 25 who provided residential treatment to those intending to stop smoking (namely, already beyond the contemplation stage) and found that the elderly with a longer smoking duration were more likely to quit 25 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the meantime, those ever having cessation advice from others and with shorter smoking years were associated with higher forward transition for those in the preparation stage. These results are consistent with Ho et al 25 who provided residential treatment to those intending to stop smoking (namely, already beyond the contemplation stage) and found that the elderly with a longer smoking duration were more likely to quit 25 .…”
Section: Discussionsupporting
confidence: 90%
“…The smoking cessation aids provided by healthcare professionals have been demonstrated as effective for those intending to stop smoking. Some studies on 3-day to 8-day residential programs with professional counseling and pharmacotherapy have demonstrated their effectiveness [25][26][27][28][29] . These studies targeted smokers who were willing to quit smoking or even in the state of nicotine dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have also demonstrated that a three-day residence program is more cost-effective than a long-term residence program. Exclusive smoking cessation camps should be conducted for women [ 27 ]. This will help mitigate any barriers they may face in terms of entering treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the residential program could be easily applied in other contexts and medical centers. This study builds on several uncontrolled and cohort studies that indicate significantly higher abstinence rates from more intensive residential smoking cessation programs than can be expected from an outpatient therapy program [21,[38][39][40][41][42][43][44]. Before a residential model of smoking cessation should be recommended for use in routine care, randomized controlled data on long-term efficacy is needed.…”
Section: Discussionmentioning
confidence: 99%
“…These relate to uncontrolled or cohort studies with limited methodological quality. However, outcomes suggest significantly increased 6-month or 12-month abstinence rates from 42.6 to 64.7% [21,[38][39][40][41][42][43]. In a large American cohort study with 226 residential smokers, Hays et al [21] reported significantly higher 6-month abstinence rates of 52% from 8-day residential smoking cessation therapy directly compared to 27% in outpatient therapy with 4327 patients, conducted from the same research group.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%